Contra-lateral Auditory Brainstem Responses in Dyslexia - AKBARI, Mehdi; JOGHATAEI, Mohammad Taghi; NOORBAKHT, Akram; JENABI, Mohammad Sadegh (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Akbari M, Joghataei MT, Poorbakhat A, Jenabi MS. Contra-lateral auditory Brainstem Responses in Dyslexia. Iran J Child Neurol. Autumn 2016; 10(4): 10-15. Abstract Objective Dyslexia is a neurological dysfunction (also known as a learning disability) that characterized by disability in reading in spite of normal intelligence. Bothe genetic and environmental risk factors are contributing into the condition. Diagnosis of dyslexia is based on examination and investigation of the patient’s memorial, spelling, visual, and reading skills. It is the most common learning disability, affecting 3%–10% of the school population. Modern neuroimaging techniques such as functional magnetic resonance imaging (fMRI) have shown a correlation between both functional and structural differences in the brains of children with reading difficulties. Hence, to address this issue, the auditory brainstem responses of children with dyslexia were investigated. Materials &Methods Fifty two children with dyslexia (30 males, 22 females) were selected after examination by speech therapist. In addition, fifty two control children were included as well. The IPSI and contralateral ABR tests were conducted on both cases and controls. Click stimuli were used at 75 nHL intensity. The study focused on absolute latency of wave V in both groups. Results Absolute latency of wave V in contralateral showed differences between children with dyslexia and control group, but no significant results were found in IPSI testing. Conclusion The current data provide an evidence for brainstem and its function in signal processing and the role of brainstem nucleus on processing and delivering the information to each hemisphere. References 1. Lyon GR, Shaywitz SE, Shaywitz BA. A definition of dyslexia: partI - defining dyslexia, comorbidity, teachers’ knowledge of language and reading. Ann Dyslexia; 2003: 53:1-14. 2. Vellutino, F, Fletcher, J,Snowling, M, &Scalon, D. Specific reading disability (dyslexia): what have we learnt in the past four decades? Child Psychology and Psychiatry; 2004: 45: 2–40 3. Demonet JF, Taylor MJ, Chaix Y. Developmental dyslexia. Lancet; 2004. 4. Wible B, NicolT, Kraus N. Correlation between brainstem and cortical auditory Brain. 2005; 128: 417–42. 5. Tzounopoulos T, Kraus N. Neuron. Learning to Encode Timing: Mechanisms of Plasticity in the Auditory Brainstem 2009; 62(4): 463–469. 6. Jeffery A, Winer.Decoding the auditory corticofugal systems Hearing Research (2005).207; 1–9. 7. Kraus N, Nicol T. Brainstem origins for cortical “what” and “where” pathways in the auditory system. Trends in Neurosciences. 2005; 28: 176-181. 8. KrishnanaA, XuaY, Gandoura J, Carianib P. Encoding of pitch in the human brainstem is sensitive to language experience. Cognitive Brain Research. 2005; 161 – 168. 9. Adams, M. Beginning to read: thinking and learning about print. Cambridge, Mass. MIT Press. 1990. 10. Demb, JB, Boynton G, M., &Heeger, D. J. Functional magnetic resonance imaging of early visual pathways in dyslexia. Neurosci. 1998; 18(17): 6939-6951. 11. Fiez, JA,Petersen, SE. Neuroimaging studies of word reading. PNAS. 1998; 95:914-921. 12. Hinshelwood J. Congenital word blindness. London: Lewis. 1917. 13. Morgan, WP. A case of congenital word blindness. The British Medical Journal. 1896; 2: 1378. 14. Dejerine, Suruncas de cectieverbale avec agraphie, suivid’autopsie. CR Soc. 1891; 43: 197–201. 15. Drake WE. Clinical and pathological findings in a child with a developmental learning disability. J Learn Disabil. 1968; 1: 486–502. 16. Orton ST. Reading, writing, and speech problems in children and selected papers. Austin: ProEd. 1937. 17. Geschwind, N, Galaburda, AM. Cerebral lateralization: Biological mechanisms, associations, and pathology. Cambridge, MA: MIT Press. 1987. 18. Weintraub S, Mesulam MM. Developmental learning disabilities. Arch Neurol. 1983;40(8):463-8. 19. Cohen L, Dehaene S. Neuroimage Specialization within the ventral stream.2004; 22(1):466-76. 20. Simos PG1, Fletcher JM, Bergman E, Breier JI, Foorman BR, Castillo EM, Davis RN, Fitzgerald M, Papanicolaou AC. Neurology. 2002;58(8):1203-13. 21. Wible, B, Nicol, T, Kraus N. Correlation between brainstem and cortical auditoryprocesses in normal and language-impaired children. Brain. 2005; 128: 417–423. 22. Starr A, Picton T, Sininger Y, Hood I, Berlin C. Auditory neuropathy. Brain. 1996; 119:741-753. 23. Zhang, Y. and Suga, N. Corticofugal feedback for collicular plasticity evoked by electric stimulation of the inferior colliculus. Neurophysiol. 2005; 94: 2676–2682. 24. Hood L J. Clinical applications of the auditory brainstem response. Singular Publishing Group. 1998; 49-63. 25. Dobie R A, Berlin C I. Binaural interaction in human auditory evoked responses. Archives of Otolaryngology. 1979; 105: 391-398. 26. MollerA R, Jannetta P J. Auditory evoked potentials recorded from the cochlearnucleus and its vicinity in man. Journal of Neurosurgery. 1983; 59(6): 1013–1018. 27. Moller A R, Jho H D, Yokota M, Janetta P J. Contribution from crossed and uncrossed brainstem structures to the brainstem auditory evoked potentials: a study in humans. Laryngoscope. 1995; 105(6): 596–605. 28. Wible B, Nicol T, Kraus N. Correlation between brainstem and cortical auditory processes in normal and language-impaired children. Brain. 2005; 128, 417–423. 29. Stone J L, Calderon-Arnulphi M, Watson K S. Brainstem auditory evoked potentials- a review and modified studies in healthy subjects. Journal of Clinical Neurophysiology. 2009; 26(3): 167–175. 30. Parkkonen L, Fujiki N, Mäkelä J P. Sources of auditory brainstem responses21 revisited: contribution by magnetoencephalography. Human Brain Mapping. 2009; 30(6): 1772–1782. 31. Møller AR, Jho HD, Yokota M, Jannetta PJ. Contribution from crossed and uncrossed brainstem structures to the brainstem auditory evoked potentials: a study in humans. Laryngoscope. 1995; 105(6):596–605. 32. Voordecker P, Brunko E, Beyl Z D. Selective unilateral absence or attenuationof wave V of brain-stem auditory evoked potentials with intrinsic brain-stem lesions. Archives of Neurology.1988; 45(11), 1272–1276. 33. Litovsky R Y, Fligor B J, Tramo M J. Functional role of the human inferiorcolliculus in binaural hearing. Hearing Research.2002; 165(1–2): 177–188. 34. Tzounopoulos T, Kraus N. Learning to encode timing: mechanisms of plasticity in the auditory brainstem. Neuron. 2009; 62(4): 463–469. 35. Hatanaka T, Shuto H, Yasuhara A, Kobayashi Y. Ipsilateral and contralateral recordings of auditory brainstem responses to monaural stimulation. Pediatric Neurology. 1988; 4(6): 354–357.